Peningkatan Religiusitas Santri Melalui Pembelajaran Fiqih di Pondok Pesantren Miftahul Huda - Riza Rizkiyah Anur Azizah; Anggita Dewi Ayu Lestari; Milatun Hasanah (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2023)
Islamic education in boarding schools plays an important role in the creation and development of students' religious identity. One of the subjects in Islamic boarding schools is fiqh which discusses the understanding and application of Islamic law in everyday life. This study aims to determine the role of fiqh teaching in improving the religiosity of students at Miftahul Huda Islamic boarding school. This research method uses qualitative methods and observation or direct observation and data analysis. The respondents in this study were administrators and students of Miftahul Huda Islamic boarding school. The data obtained were analyzed using data reduction, data display, and conclusion drawing. The results showed that fiqh learning at Miftahul Huda Islamic Boarding School had a significant impact in increasing the religious awareness of the students. The fiqh teaching provides a deep understanding of Islamic teachings and procedures for worship. The students must be able to apply this fiqh knowledge in their daily lives, both in social interactions and in their worship to Allah SWT.  In addition, fiqh teaching also helps students understand the importance of social responsibility, morals, ethics and morality in Islam. This encourages them to be responsible individuals, care for others, and behave well in society. Overall, the teaching of fiqh at Miftahul Huda Islamic Boarding School plays an important role in increasing the religious awareness of the santri. Therefore, the boarding school needs to continue to improve the quality of fiqh teaching in order to produce students who have strong faith and religious deeds.